Reconstruction for axillary hidradenitis suppurativa using one‐stage local tissue rearrangement: A retrospective analysis of 53 cases. Issue 3 (18th February 2020) - Wu, Yinglun; Ngaage, Ledibabari M; Ge, Shealinna; Rada, Erin M.; Silverman, Ronald P.; Rasko, Yvonne M.
Abstract: Wide local excision offers a potential cure for severe axillary hidradenitis suppurativa. However, the gold standard for reconstruction has yet to be defined. Here, we describe our rotation advancement flap technique, which allows for one‐stage closure of large axillary defects, with minimal functional morbidity to the axilla. We performed a retrospective review of all patients who underwent one‐stage surgical management for axillary hidradenitis suppurativa at a single‐centre tertiary care hospital from 2009 to 2018. We identified 34 patients, with a total of 53 operative sites. The majority were female (85%) with a mean age of 31 years and body mass index 35 kg/m 2 . The median defect size was 84 cm 2 and the majority were treated using the rotation advancement flap technique (86%). A quarter of operative sites experienced minor complications with only one requiring re‐operation. At a median follow‐up of 32 months, two (4%) sites showed decreased range of motion. However, all patients had achieved remission without any further recurrence of disease. We describe a one‐stage rotation advancement flap technique for management of moderate to severe hidradenitis suppurativa that achieves a high local cure rate, minimal functional morbidity, and acceptable wound complication rates.